Survey of viral hemorrhagic septicemia virus (VHSV) in olive flounder, Paralichthys olivaceus hatchery in Korea - Jang, Min-Seok; Oh, Myung-Joo; Kim, Seok-Ryel; Kim, Wi-Sik (Penerbit Universiti Kebangsaan Malaysia, 2019)
Viral hemorrhagic septicemia (VHS) generally occurs after juvenile olive flounders (Paralichthys olivaceus) are moved from the hatchery to on-growing system in Korea during spring. However, it remains unclear whether fish are infected by VHS virus (VHSV) in the hatchery or the on-growing system. In the present study, a survey was conducted to investigate VHSV infection in 39 olive flounder hatcheries from 2014 to 2017. Fish were tested for the presence of VHSV by inoculating sample to fathead minnow (FHM) and chinook salmon embryo (CHSE-214) cells to observe cytopathic effect, reverse transcription-polymerase chain reaction (RT-PCR), and antibody detection enzyme-linked immunosorbent assay (ELISA). VHSV was not detected in any of the 2,430 fish (from 461 pooled and 156 unpooled samples), although 34 (20.3%) of 167 samples was found to be positive for marine birnavirus (MABV) by cell culture and RT-PCR. Antibody detection ELISA results showed that all 212 fish sera have optical density (OD) values below of 0.1, suggesting that these fish had no VHSV-specific antibodies. Moreover, VHSV was not detected in any of 40 pooled samples (172 fish) collected after shifting rearing water temperature from 17-21°C to 10-15°C. In conclusion, the 39 olive flounder hatcheries surveyed in Korea was not infected by VHSV.